Strategi Komunikasi Dinas Lingkungan Hidup dalam Meningkatkan Partisipasi Masyarakat pada Pengelolaan Sampah di Kota Padang - Maimona Sasmita; Dion Eriend (CV. ITTC INDONESIA, 2026)
Urban waste problems in Padang City remain a serious challenge in creating a clean and sustainable environment. The low level of public awareness in sorting and managing waste has become one of the factors affecting the success of waste management programs implemented by the local government. This study aims to analyze the communication strategy of the Environmental Agency of Padang City in increasing community participation in waste management. This research employed a descriptive qualitative method with a case study approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation. The research informants consisted of officials from the Environmental Agency, community leaders, and members of the community involved in waste management programs. Data analysis techniques used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results showed that the communication strategy was carried out through interpersonal socialization based on neighborhood associations (RT/RW), the use of social media, outdoor media such as banners and billboards, and the strengthening of community-based waste bank programs. These strategies were considered effective in increasing public awareness and participation in waste management. However, the implementation of the program still faces obstacles, including the low awareness of some community members and the habit of disposing of waste improperly. Therefore, sustainable and collaborative communication strategies are needed to support the effectiveness of waste management in Padang City.